Correlation of cardiovascular risk predictors with overweight and obesity in patients with familial hypercholesterolemia - Wang, Yaodong; He, Jinchun (Frontiers in Cardiovascular Medicine, 2022)
PURPOSE: We aimed to analyze the correlation between overweight and obesity-related indicators and cardiovascular risk predictors in patients with familial hypercholesterolemia (FH) and to evaluate their mutual predictive properties. METHODS: 103 patients with FH included from 2004 to 2017 were retrospectively analyzed. Pearson correlation analysis and multiple linear regression analysis were used to assess the correlation between overweight and obesity-related indicators and cardiovascular risk predictors in FH patients. Subject operating characteristic (ROC) curve was used to analyze their reciprocal predictive performance. RESULTS: (1)Atherogenic index of plasma (AIP) (β = 0.020,) and ApoB/ApoA1 Ratio (BAR) (β = 0.015) were independently correlated with body mass index (BMI) (P <0.05); AIP (β = 1.176,) was independently correlated with waist-to-hip ratio (WHR) (P <0.01); AIP (β = 1.575), BAR (β = 0.661) and atherogenic coefficient (AC) (β = 0.427) were independently correlated with waist-to-height ratio (WHtR) (P<0.05). (2)The area under the ROC (AUC) for overweight corresponding to AIP, BAR, and AC were 0.695 (95% CI = 0.593-0.797, P<0.01), 0.660 (95% CI = 0.555-0.766, P<0.01), and 0.632 (95% CI = 0.525-0.740, P<0.05), respectively; and AUCs for central obesity corresponding to AIP, BAR and AC were 0.757 (95% CI = 0.656-0.857, P<0.001), 0.654 (95% CI = 0.536-0.771, P<0.05) and 0.651 (95% CI = 0.538-0.764, P<0.05), respectively. The AUCs for moderate risk of AIP corresponding to BMI, WHR and WHtR were 0.709 (95% CI = 0.608-0.811, P<0.001), 0.773 (95% CI = 0.678-0.867, P<0.001), 0.739 (95% CI = 0.641-0.836, P < 0.001), respectively, and BMI , WHR and WHtR corresponded to an AUC of 0.691 (95% CI = 0.585-0.797, P <0.01), 0.734 (95% CI = 0.632-0.835, P<0.001), and 0.706 (95% CI = 0.603-0.810, P<0.01) for high risk of AIP, respectively. CONCLUSIONS: AIP has independent positive linear correlation with indicators related to overweight and obesity in FH patients; AIP has good predictive performance for overweight and obesity in FH patients, and WHR has good performance for identifying moderate and high risk of AIP in FH patients.